2021
DOI: 10.17557/tjfc.1038570
|View full text |Cite
|
Sign up to set email alerts
|

CRITICAL DOSE OF NITROGEN AND PHOSPHORUS FOR THE ENHANCED GROWTH, YIELD, AND QUALITY COMPONENTS IN MUSTARD (Sinapsis arvensis L.) IN A SEMI ARID ENVIRONMENT

Abstract: Mustard grows in many parts of the world thanks to its ability to adapt to different climatic conditions. It has the potential to be an important oilseed plant especially in the east of Turkey. There is scarcely any information available about fertilization in mustard cultivation in Turkey. Nitrogen and phosphorus fertilizers, a good source of nutrients for the soil, have a positive effect on the growth, development, and yield of the plant in case they are applied at the optimum level. This study was carried o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…The difference between the years might be due to higher precipitation occurring in growing months (October-April) during 2019-2020, as compared to in 2020-2021 (Table 2). It was also previously reported by Öztürk et al [45] that high precipitation may cause higher oil contents in the crop. In the current study, at a level of 100 kg•ha −1 N, maximum protein contents were noted.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The difference between the years might be due to higher precipitation occurring in growing months (October-April) during 2019-2020, as compared to in 2020-2021 (Table 2). It was also previously reported by Öztürk et al [45] that high precipitation may cause higher oil contents in the crop. In the current study, at a level of 100 kg•ha −1 N, maximum protein contents were noted.…”
Section: Discussionsupporting
confidence: 75%
“…According to Sokólski et al [44], nitrogen fertilizer had the most positive effect on TSW. Further, Öztürk [45] also stated that the 100 kg•ha −1 level of N caused an increase in the TSW of a brassica crop. Our results regarding the increase in TSW after the application of N fertilizer were supported by Williams et al [46], who concluded that the brassica species are high nitrogen-demanding crops, and thus respond positively to optimum or near-optimal N application.…”
Section: Discussionmentioning
confidence: 99%